ANALISIS STRUKTUR LAPISAN BAWAH PERMUKAAN MENGGUNAKAN METODE GEOLISTRIK (STUDI KASUS PADA KAMPUS III IAIN IMAM BONJOL PADANG DI SUNGAI BANGEK KECAMATN KOTO TANGAH) (JURNAL SPASIAL, 2015)
The purpose of this research is to know about the structure of subsurface in campus III IAIN Imam Bonjol Padang. Information about subsurface used to preeleminary research as a base of planning office and classroom on new campus IAIN Imam Bonjol at Sungai Bangek. This Research use geophysical properties, specially Geoelectrical method. Geoelectrical method use electrical property of the earth through the subsurface and then record by geophone on the surface. The interpretation of the subsurface was do according to different of their resistivity. The result of this research shows that structure of this area dominate by clay, limestone, and andesit. The surface dominate by clay, andesit only in a few area. In subsurface andesit in range 45-60 meter.Kata Kunci: Structure of subsurface, geoelectric, clay, limestone, andesit